The Relationship Between Nutritional Intake and Behavioral Factors on the Incidence of Anemia in Female Adolescents in Senior High Schools in Jambi City - Ibnu, Ismi Nurwaqiah; Sitanggang, Hendra Dhermawan; Enis, Rina Nofri (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2025)
Adolescents are one of the high-risk groups for anemia. Adolescent girls who experience anemia and chronic energy deficiency are at risk of becoming stunted mothers. This study aims to identify the prevalence and determinants of adolescent girls that increase the risk of anemia in Jambi City. This study is an analytical study using a cross-sectional research design. The study was conducted from July to November 2024. The population in this study were all female high school students in Jambi City in 2023, namely 6878 students. The minimum sample in this study was 201 female adolescents, who were divided into 6 public secondary schools that were randomized in clusters, grade XI female students, did not experience chronic/acute diseases related to bleeding. The variable of hemoglobin levels was measured by direct examination, the consumption variable was interviewed using a semi-FFQ questionnaire. Knowledge and attitude variables about anemia were also collected using a validated questionnaire. Univariate and bivariate tests and to measure the magnitude of risk using the SPSS data analysis program application. The results of this study are the prevalence of anemia in adolescent girls, namely 131 adolescents (64.7%) and the prevalence of chronic energy deficiency of 89 adolescents (44.3%). The conclusion is that the factors that influence the incidence of anemia in adolescent girls in Jambi City are carbohydrate intake (p.value = 0.033), protein intake (p-value = 0.000), iron intake (p.value = 0.000), zinc intake (p.value = 0.021), knowledge about anemia (p.value = 0.000), and attitudes towards anemia. (p.value = 0.000).